Neural networks based mesh generation method in 2-D - Ahmet, Ç; Ahmet, A (Springer-Verlag Berlin, 2002)
This paper describes a novel method for mesh generation in 2D by means of feed forward single layer neural networks. Original values of an initially given boundary are represented by finite values instead whole of points. For this aim, b-spline control points are made up to boundary curve. The obtained control points are used as inputs of the single layer feed forward neural network and points which belongs to closed area are obtained from output of neural networks. Obtained points are meshed by proposed method. As application, some mesh samples are given.
1st EurAsian Conference on Advances in Information and Communication Technology (EurAsia-ICT 2002) -- OCT 29-31, 2002 -- SHIRAZ, IRAN
Keywords: Grid Generation